Paranoid personality type: Relationships with the surroundings - L. Spytska (Mukachevo State University, 2023)
The relevance of the study lies in the fact that the transience of changes in the social surrounding requires dynamism and competitiveness from a person, which forces the individual to actively transform the emotional regulation of behaviour, in particular in communication and relationships. However, the adaptive capabilities of a person who is characterised by increased sensitivity to frustration and persistent distrust of others can be considerably limited, and therefore maintaining the mental health of people at risk has become an urgent issue. The purpose of the study is to determine the basis on which character anomalies are formed, to uncover the cause-and-effect relationships in the issue of the development of mental disorders, and to identify possible ways to overcome complications in relationships with the surroundings caused by disturbances in mental activity. At the core of the theoretical and methodological approach lies the combination of methods involving structural-functional analysis of the issue of forming a paranoid personality type and an analytical investigation of the psychological support methods for neuro-mental disorders that affect individual behavioural self-regulation. The empirical basis of the study is questionnaires and diagnostics of the mental states of people prone to personality disorders. The paper clarifies the causes and features of the development of paranoid mental anomalies and the possibilities of prevention and correction of such mental disorders. The presented results reflect the problem of the adaptive capabilities of people with congenital or acquired pathological conditions of the psyche. The paper covers the issues of interaction with the paranoid personality type socially. The most popular concepts of providing psychological assistance are considered. The correctness of the assumption that it is much more difficult for people with a paranoid personality type to cope with frustration and adapt to society is analysed. The results obtained are of practical value for social workers who are engaged in identifying mental health disorders of people at risk and predicting deviant behavioural responses, for practical psychologists who support people with a paranoid personality type, in particular through psychotherapy.